Chronology of the Early Toarcian environmental crisis in the Lorraine Sub-Basin (NE Paris Basin) - Ruebsam, W.; Munzberger, P.; Schwark, Lorenz (Elsevier Science BV, 2014)
Early Toarcian (Jurassic; ~183Ma) sediments recorded profound environmental changes, including mass extinction, global warming, marine transgression as well as widespread bottom water anoxia and organic matter accumulation on the Western Tethyan shelf. Enhanced organic matter accumulation was accompanied by a positive carbon isotope excursion (CIE) in pelagic carbonate, which marks the Toarcian Oceanic Anoxic Event. These environmental changes were accompanied by a major perturbation of the global carbon cycle, expressed by negative CIE, interrupting the positive trend. The duration of the carbon cycle perturbation is still debated, with estimates for the negative CIE range from ~200 to ~600kyr. Here we present ultra high-resolution (<1kyr) measurements of magnetic susceptibility and sediment color from a marine section located in the Lorraine Sub-Basin (NE Paris Basin) documenting Milankovitch-controlled fluctuations in depositional conditions that occurred superimposed onto the overall sea level evolution. Differences in the wavelength of the sedimentary cycles indicate variable sediment accumulation rates that mainly resulted from rapid sea level fluctuations. The most pronounced sea level rise that took place within the uppermost tenuicostatum zoneresulted in a strong condensation of the basal Schistes Carton formation. Strong condensation can explain the discrepancy between durations previously calculated for the CIE placed at this stratigraphic interval. Our data support durations of ~900kyr and ~600kyr for the positive and negative CIE, respectively. The cyclostratigraphy-based timescale further proposes a duration of >555kyr for the tenuicostatum zoneand 1310kyr for the serpentinum zone. The durations of the elegantulumand falciferumsubzonescan be estimated to ~790kyr and ~520kyr, respectively. A change in the orbital response from eccentricity-to obliquity-forcing, evident from other locations, is well-expressed in the Lorraine Sub-Basin and occurred within the CIE interval. The strong impact of the obliquity component in post-event deposits hints to processes most effective at high latitudes, such as the waxing and waning of polar ice. Paleogeographic features of the Western Tethyan shelf supported the tele-connection of higher to lower latitude processes via water exchange through the Viking Corridor.